Prognostic value and immunomodulatory role of DNM1L in gastric adenocarcinoma - Zhao, Zhuo; Li, Lingxia; Liu, Yan; Shi, Lei; Yuan, Meijie; Shi, Hongshuo; Ji, Qing (Frontiers in Oncology, 2024)
BackgroundMitochondrial fusion and fission are critical for the morphology and function of cells. DNM1L encodes dynamin-related protein 1 (DRP1), a key protein mediating mitochondrial fission, which is upregulated in a variety of cancers and is strongly associated with tumorigenesis. We aim to investigate the relationship between DNM1L and the prognosis of gastric cancer, as well as to explore the function and mechanism of DNM1L in gastric cancer (GC).Materials and methodsIn this study, we analyzed the expression differences of DNM1L in gastric cancer tissues and paracancerous tissues using The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) database. This was followed by validation through tissue microarrays. We then utilized the cohort information from these microarrays to explore the relationship between DNM1L expression and gastric cancer prognosis. Furthermore, we conducted enrichment analysis to investigate the function and mechanisms of DNM1L in gastric cancer, and lastly, we performed immune cell infiltration analysis using the CIBERSORT algorithm.ResultsWe discovered that the expression of DNM1L is elevated in GC tissues. TCGA data showed that the overexpression of DNM1L was positively correlated with the T-stage of GC but not with lymph node metastasis, which was also corroborated by our immunohistochemistry experiments. Based on the Kaplan–Meier curves, the high DNM1L expression was remarkably correlated with poor overall survival in patients with GC. In addition, results of COX regression analysis indicated that high DNM1L expression was an independent prognostic factor in patients with GC. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene set enrichment analysis (GSEA) showed that DNM1L was closely associated with multiple signaling pathways and immune responses. CIBERSORT analysis indicated that increased DNM1L expression may affect the infiltration of immune cells in the tumor microenvironment.ConclusionThe results of this study indicate that DNM1L is upregulated in gastric cancer (GC) and positively correlates with the T-stage and poor prognosis of GC patients, and it plays an important role in tumor immune infiltration.